Designing Typeface for Nginden Herbal Tourism Village - Aileena Solicitor Costa Rica El Chidtian (Nusantara Science and Technology Proceedings, 2022)
Typography cannot be separated from visual communication design as one of the elements in it. In typography, there is the term Typeface which is a letter with characteristics that are more focused on the design of the letterform used. The use of letters is not only limited to communication media but can also function as an identity and educational media which in this case is in the form of education about herbal plants. This typeface design explores and uses elements of herbal plants with other visual literacy that is identical to the Nginden Herbal Tourism Village in Surabaya. The results of the typeface design with elements of the local culture are expected to provide a distinctive identity for the tourist village and help enrich the diversity of local Indonesian typography which at the same time raises the image of the Nginden Herbal Tourism Village in Surabaya with the introduction of typeface widely using internet media.